Abortion Bans, Doctors, and the Criminalization of Patients - Oberman, Michelle (The Hastings Center report, 2018)
January 2018, the American College of Obstetrics and Gynecology issued a position statement opposing the punishment of women for self-induced abortion. To those unfamiliar with emerging trends in abortion in the United States and worldwide, the need for the declaration might not be apparent. Several studies suggest that self-induced abortion is on the rise in the United States. Simultaneously, prosecutions of pregnant women for behavior thought to harm the fetus are increasing. The ACOG statement responds to both trends by urging doctors to honor the integrity and confidentiality inherent in the doctor-patient relationship. Seen in the context of the larger battle over legal abortion, the statement has far broader implications. By acknowledging the role doctors play in enforcing pregnancy-related crimes, the ACOG position statement wisely anticipates the ways in which doctors will be implicated should access to legal abortion be further restricted. To understand the need for the ACOG directive, you must first understand that the story of what will happen if abortion becomes a crime in the United States is not to be found in history books; it is staring at us across our southern border.